Cyborg insect factory: automatic assembly for insect-computer hybrid robot via vision-guided robotic arm manipulation of custom bipolar electrodes - Qifeng Lin; Nghia Vuong; Kewei Song; Phuoc Thanh Tran-Ngoc; Greg Angelo Gonzales Nonato; Hirotaka Sato (Nature Communications)
Abstract Insect–computer hybrid robots offer strong potential for navigating complex terrains. This study identified the intersegmental membrane between the pronotum and mesothorax of the Madagascar hissing cockroach as an effective site for electrical stimulation to control direction and speed. A pair of bipolar electrodes was custom-designed, and an automatic assembly system was developed, integrating a robotic arm, vision-based site detection, and an insect fixation structure. The system achieved assembly in 68 s. Hybrid robots exhibited robust steering (over 70°) and deceleration (68.2% speed reduction) with performance comparable to manually assembled counterparts. Controlled navigation along an S-shaped path confirmed accurate directional control. Furthermore, a multi-agent system of four hybrid robots covered 80.25% of an obstructed terrain in 10 minutes and 31 seconds. This work demonstrates a scalable strategy for automating the fabrication of insect–computer hybrid robots, enabling efficient and reproducible assembly process while maintaining effective locomotion control.